An Experimental Study on Heat Conduction and Thermal Contact Resistance for the AlN Flake - Huann-Ming Chou; Jin-Chi Wang; Yuh-Ping Chang (Advances in Materials Science and Engineering)
The electrical technology has been a fast development over the past decades. Moreover, the tendency of microelements and dense division multiplex is significantly for the electrical industries. Therefore, the high thermal conductible and electrical insulating device will be popular and important. It is well known that AlN still maintains stablility in the high temperature. This is quite attractive for the research and development department. Moreover, the thermal conduct coefficient of AlN is several times larger than the others. Therefore, it has been thought to play an important role for the radiator of heat source in the future. Therefore, this paper is focused on the studies of heat conduction and thermal contact resistance between the AlN flake and the copper specimens. The heating temperatures and the contact pressures were selected as the experimental parameters. According to the experimental results, the materials are soft and the real contact areas between the interfaces significantly increase under higher temperatures. As a result, the thermal contact resistance significantly decreases and the heat transfer rate increases with increasing the heating temperature or the contact pressures.